A review on assessment and treatment for depression in Malaysia. - Mukhtar, Firdaus; Tian, P. S. Oei (Hindawi Publishing Corporation, 2011)
This paper aimed to review the literature on depression that focused on its assessment and treatment in Malaysia. PsycINFO, Medline, local journals were searched, and 18 published articles were included in this paper. Results indicate that research on depression in Malaysia, particularly validation studies and psychotherapy research, was weak and fragmented, with minimal empirical evidence available. Pharmacotherapy still dominated the treatment for depression, and, in terms of psychotherapy, Cognitive Behavioural Therapy (CBT) was recently practiced, but only a few studies have reported on the treatment efficacy of CBT. Major limitations of studies were noted, and, consequently, the problems that are associated with the implementation and future direction of clinical and research on depression in Malaysia were discussed. In short, the contribution of empirical research on the assessment and treatment for depression remained inconsistent and fragmented and urgently in need of further empirical investigation.